Use of a vascular closure device during percutaneous arterial access in a dog with impaired hemostasis. Issue 4 (23rd May 2017) - Scansen, Brian A.; Hokanson, Caitlin M.; Friedenberg, Steven G.; Khabiri, Hooman
Abstract: Objective: To report the use of a vascular closure device (VCD) to provide rapid arterial hemostasis following percutaneous femoral arterial catheterization and diagnostic angiography in a thrombocytopenic and coagulopathic dog. Case Summary: A 6‐year‐old female spayed Kai Ken Tora dog presented after vehicular trauma. The dog was diagnosed with traumatic pneumothorax, degloving wounds of the right antebrachium, subcutaneous hemorrhage within the axillary tissues of the left thoracic limb, and anemia and thrombocytopenia secondary to acute hemorrhage. Treatment included therapeutic thoracocentesis and open wound management of the right thoracic limb as well as packed RBC and fresh frozen plasma transfusions. Diagnostic angiography of the left brachial artery was performed via percutaneous femoral arterial access to investigate the source of a persistent axillary hematoma. The arterial access site was closed using an extraluminal VCD and hemostasis was immediate with normal femoral arterial blood flow documented by Doppler ultrasound. New or Unique Information Provided: This report describes use of a VCD for arterial closure following percutaneous access in a dog with impaired hemostasis; to the authors' knowledge, this is the first clinical report of a VCD used in a veterinary species.